Metoidioplasty: Surgical Options and Outcomes in 813 Cases - Bordas, Noemi; Stojanovic, Borko; Bizic, Marta; Szanto, Arpad; Djordjevic, Miroslav L. (Frontiers in Endocrinology, 2021)
Introduction: Metoidioplasty is a variant of phalloplasty for transmen that includes the creation of the neophallus from a hormonally enlarged clitoris, urethral lengthening and scrotoplasty. The procedure results in male appearance of genitalia, voiding in standing position and preserved sexual arousal, but without possibility for penetrative intercourse. We evaluated outcomes of metoidioplasty at our center, based on latest surgical refinements. Methods: During the period of 14 years (from February 2006 to April 2020), 813 transmen with mean age of 24.4 years and mean body mass index of 24.6, underwent one stage metoidioplasty. Hysterectomy was simultaneously performed in 156, and mastectomy in 58 cases. Hysterectomy, mastectomy and metoidioplasty were done as a one-stage procedure in 46 transmen. Patients are divided in 5 groups, depending on the type of urethroplasty. Postoperative questionnaires were used to evaluate cosmetic and functional outcomes, as well as patients' satisfaction. Results: Follow-up ranged from 16 to 180 months (mean 94 months). Mean surgery time was 170 minutes and mean hospital stay was 3 days. Length of the neophallus ranged from 4.8 cm to 10.2 cm (mean 5.6 cm). Urethroplasty was complication-free in 89.5% of cases, and ranged between 81% to 90.3% in different groups. Urethral fistula and stricture occured in 8.85% and 1.70% of cases, respectively. Other complications included testicular implant rejection in 2%, testicular displacement in 3.20% and vaginal remnant in 9.60% of cases. From 655 patients who answered the questionnaire, 79% were totally satisfied and 20% mainly satisfied with the result of surgery. All patients reported voiding in standing position and good sexual arousal of the neophallus, without possibility for penetrative intercourse due to small size of the neophallus. Conclusion: Metoidioplasty has good cosmetic and functional outcomes, with low complication rate and high level of patients' satisfaction. In transmen who request total phalloplasty after metoidioplasty, all available phalloplasty techniques are feasible.